Creative Process and Co-Research with the Early Years through Flight - Ayles, Robyn; Fitzsimmons Frey, Heather; Leach, Jamie (Performance Matters, 2023)
Practice-based research that meaningfully engages with very young children (ages eighteen months to five years) as co-researchers presents wonderful opportunities to co-imagine possibilities together, but it also presents challenges related to communication, a democratic process, and children’s agency. In this article, we discuss how The Urban Wildlife Project uses Flight: Alberta’s Early Learning and Care Framework to help our creative team have a relationship-centred process. We discuss how Flight’s core values of play and playfulness inform our process, how Flight’s “Cycle of Co-Inquiry” and emphasis on understanding children’s meaning-making honours children as citizens, and how several key concepts--including “co-,” a specific conception of children and childhood, play and play-informed meaning-making, and making magic--enable us to include very young children as co-researchers in our co-creation and co-imagination practices.  To illuminate how the process works, we offer two examples of how we are using Flight to inform our practice-based research processes with the early years demographic, and to create meaningful immersive theatre experiences for all participants.